2005
DOI: 10.1002/qua.20716
|View full text |Cite
|
Sign up to set email alerts
|

Molecular modeling study of binding to the catalytic site of PDE4 enzymes by a novel class of inhibitors

Abstract: Cyclic nucleotide phosphodiesterases (PDEs) comprise a superfamily of enzymes that hydrolyze the second messengers adenosine and guanosine 3Ј,5Ј-cyclic monophosphate (cAMP and cGMP) to their noncyclic nucleotides (5Ј-AMP and 5Ј-GMP). Selective inhibitors of all 11 gene families of PDEs are being sought based on the different biochemical properties of the different isoforms, including their substrate specificities. The PDE4 gene family consists of cAMP-specific isoforms; selective PDE4 inhibitors such as rolipr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…Computational studies on PDEs have also been reported in the literature. For example, molecular dynamics (MD) simulations and hybrid quantum mechanics/molecular mechanics (QM/MM) calculations have been employed to characterize the bridging ligand between the two metal ions and other structural problems in the PDE active site. ,,, Zagrovic et al have employed thermodynamic integration to study the binding affinities of several inhibitors toward PDE5. , …”
Section: Introductionmentioning
confidence: 99%
“…Computational studies on PDEs have also been reported in the literature. For example, molecular dynamics (MD) simulations and hybrid quantum mechanics/molecular mechanics (QM/MM) calculations have been employed to characterize the bridging ligand between the two metal ions and other structural problems in the PDE active site. ,,, Zagrovic et al have employed thermodynamic integration to study the binding affinities of several inhibitors toward PDE5. , …”
Section: Introductionmentioning
confidence: 99%
“…This is to attain the most stable conformations, and then saved as pdbqt files to be used for in silico study. Recently, several studies have been reported that the active site region of PDE4 enzyme is Tyr233, His234, Asp275, Asn283, Gln284, Glu304, Thr345, Met347, Asp392, Leu393, Asn395, Thr407, Gln433, Ile410, and Phe446 [32,35–38]. The docking approach [2,39] was performed by launching the PyRx—virtual screening software to compute the binding energy score (kcal/mol).…”
Section: Resultsmentioning
confidence: 99%
“…10 There exists quite a few recent computational studies covering several important aspects of PDEs. 19,20,[35][36][37][38][39][40][41] For example, molecular dynamics (MD) simulations and hybrid quantum mechanics/molecular mechanics (QM/MM) calculations have been employed in characterizing the bridging ligand between the two metal ions in PDE. 19,20 Wierzbicki et al have also applied the QM/MM method to study the hydrolysis of cAMP in PDE4 37 and the cyclic nucleotide recognition in different PDEs by using truncated models derived from crystal structures.…”
Section: Introductionmentioning
confidence: 99%
“…There exists quite a few recent computational studies covering several important aspects of PDEs. ,, For example, molecular dynamics (MD) simulations and hybrid quantum mechanics/molecular mechanics (QM/MM) calculations have been employed in characterizing the bridging ligand between the two metal ions in PDE. , Wierzbicki et al have also applied the QM/MM method to study the hydrolysis of cAMP in PDE4 and the cyclic nucleotide recognition in different PDEs by using truncated models derived from crystal structures. , Zagrovic et al have employed thermodynamic integration to study the binding affinities of several inhibitors toward PDE5 . More recently, Zhan et al have compared the binding affinities of several inhibitors toward PDE2 by using MD simulations and molecular mechanics/Poisson−Boltzmann surface area (MM/PBSA) methods .…”
Section: Introductionmentioning
confidence: 99%